Structural and transport properties of double perovskite Dy2NiMnO6. (February 2015) - Chanda, Sadhan; Saha, Sujoy; Dutta, Alo; Sinha, T.P.
Graphical abstract: Highlights: Sol–gel citrate method is used to prepare the double perovskite Dy2 NiMnO6 . Structure and dielectric relaxation of the sample are studied for nano and bulk phases. The relaxation mechanism of the sample is modeled by Cole–Cole equation. With increasing sintering temperature conductivity increases. Electronic structures and magnetic properties have been studied by DFT calculations. Abstract: The double perovskite oxide Dy2 NiMnO6 (DNMO) is synthesized in nano and bulk phase by the sol–gel citrate method. The Rietveld refinement of X-ray diffraction pattern of the sample at room temperature shows the monoclinic P21 / n phase. Dielectric relaxation of the sample is investigated in the impedance and electric modulus formalisms in the frequency range from 50 Hz to 1 MHz and in the temperature range from 253 to 415 K. The Cole–Cole model is used to explain the relaxation mechanism in DNMO. The frequency-dependent maxima in the imaginary part of impedance are found to obey an Arrhenius law with activation energy of 0.346 and 0.344 eV for nano and bulk DNMO, respectively. A significant increase in conductivity of bulk DNMO has been observed than that of the nanoceramic. Electronic structures and magnetic properties of DNMO have been studied by performing first principles calculation based on density functional theory.